Ionospheric Prediction and Forecasting - Zolesi, Bruno; Cander, Ljiljana R. (Springer Geophysics,, 2014)
This book describes how to predict and forecast the state of the planet Earth's ionosphere under quiet and disturbed conditions in terms of dynamic processes in the weakly ionized plasma media of the upper atmosphere, using the modern measurement and modelling techniques available. A close relationship is explained between the state of the media and the radio wave propagation features of the media. The prediction and forecasting algorithms, methods, and models are oriented towards providing a practical approach to the design and engineering of ionospherically dependent radio systems. The book also covers those aspects of ionospheric prediction and forecasting relevant to space weather phenomena and their effects on new technologies. A proper understanding of the ionosphere is of fundamental practical importance because it is an essential element in telecommunication and navigation systems, while space weather is expected to be an important factor in space-related research subjects (e.g. astronomy, solar and space physics, planetary and Earth sciences) over the next decade as ever more detailed knowledge, modelling, prediction, and forecasting of the Sun-Earth system are required.